Tiredness with words? Multimodality – a research challenge for the 21st century (text) linguistics? - Szumska, Dorota (Papers in Linguistics, 2024)
The aim of the article, as reflected in the title, is an attempt to make a contribution to the metalinguistic debate about the influence of the visual turn on research directions and quality of the 21st century linguistics, with particular regard to semantics and text linguistics. The problem is presented from two perspectives. On the one hand, the proposed analysis focuses on the opportunities offered by the communicative coexistence of the verbal code with other semiotic codes – opportunities to conduct in-depth studies of decomposition of meaning of lexical units and their combination properties, including text-forming properties. On the other hand, the article points to some research threats, such as crossing the borders of the exploratory range of linguistics, which comes with fashionable indiscriminate methodological and epistemological expansion of its research field to include multimodal content.